TINJAUAN HERMENEUTIS TERHADAP HADIS KEPEMIMPINAN PEREMPUAN DALAM ISLAM - Wahyudi Wahyudi; Nur Fadilah (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2018)
This paper discusses the hermeneutical perspective of the prohibition for women to become leaders hadith narrated by Abu Bakrah. The factor that became the background of this study is that there are still many people who understand that women are the second creature, namely "konco wingking". So, they are not deserve to be a leader for people. One of the normative bases is the hadith narrated by Abu Bakrah. The textual-literal understanding of the hadith has implications for the role of women in the public sphere so that there needs to be someone who can answer and place women to their proper degree. This study uses a qualitative method with Schleiermacher hermeneutics approach.The results of this research are the Hadith about the ban on women becoming leaders who narrated by Abu Bakrah through grammatical hermeneutics and psychological perspective cannot be applied in General. Thus, there are no restrictions for women today to be a leader for the people because they currently have a different social background when the Hadith it comes.